New luminescence dating evidence reveals the timing of Neolithic human activities in Fuzhou Basin, South China - Jin, Jianhui; Cai, Xipeng; Huang, Yunming; Zuo, Xinxin; Ling, Zhiyong; Dai, Jinqi; Ren, Yongqing; Zhang, Wenjing; Li, Shutong (Catena (Giessen), 2021)
•It is the earliest geochronological evidence for the presence of humans in coastal Fujian, China.•Ancient humans have occupied this area within mid-Holocene (6–4 ka).•Sea level change can control the spatial distribution of prehistoric sites in the estuary area.•Climate events may be one of the main factors triggering cultural transformation. The South China coastal area provides important insights into China’s prehistoric Marine life; however, the timing of ancient human activity during the Neolithic period in South China is still controversial, owing to the scarcity of a reliable chronology of archaeological sites. In this study, we presented the optically stimulated luminescence ages, which were derived from the medium-grained quartz at the Baitoushan site located along the coast of Fujian Province. Single-aliquot regenerative-dose measurements of red soil deposits from the site yielded internally and stratigraphically consistent ages (with errors) after excluding data that may be affected by sampling, thereby indicating the adequate reliability of the technique and the significant influence of field sampling process on the test results. The results showed that the ages of cultural deposit associated with the abundant sherds varied from 3.74 ± 0.21 ka to 5.96 ± 0.42 ka, thereby providing the earliest geochronological evidence for the presence of humans in the lower reach of Min River during the mid-Holocene. The period linked to Lower Tanshishan culture and Keqiutou cultures (to a first approximation) suggests a potentially favourable and moist environment; that is, ancient humans occupied this area within the mid-Holocene (6–4 ka). By a comprehensive comparison of environmental change factors, sea level change can control the spatial distribution of prehistoric sites in the estuary area, and climate events may be one of the main factors triggering cultural transformation.